Pulmonary Toxoplasmosis Diagnosed on Transbronchial Lung Biopsy in a Mechanically Ventilated Patient - Delyse Garg; Nikhil Madan; Omar Qaqish; Sandhya Nagarakanti; Vipul Patel (Case Reports in Infectious Diseases, 2020)
Toxoplasma gondii is a protozoan parasite that infects up to a third of the world’s population. Infection is mainly acquired by ingestion of food or water that is contaminated with oocysts shed by cats or consuming undercooked meat containing tissue cysts. Primary infection is subclinical in immunocompetent hosts. Invasive toxoplasmosis often manifests as cerebral toxoplasmosis in immunosuppressed patients. In persons living with human immunodeficiency virus (HIV), toxoplasmosis occurs when CD4 counts are very low and is considered an acquired immunodeficiency syndrome (AIDS) defining illness. Pulmonary toxoplasmosis is rarely seen in the highly active antiretroviral therapy era. The diagnosis can be challenging due to the nonspecific nature of clinical and radiographic findings. In this report, we present a case of pulmonary toxoplasmosis in a new onset AIDS patient, which was initially clinically misdiagnosed as Pneumocystis jiroveci pneumonia (PJP). Due to a poor response to treatment for PJP, the patient underwent a transbronchial lung biopsy, which led to the diagnosis of pulmonary toxoplasmosis.